Ethics in tendering: A survey of Australian opinion and practice - Ray, Richard S.; Hornibrook, John; Skitmore, Martin; Zarkada, Anna K. (My University, 1999)
The main issues in the philosophical foundations of ethics and tendering ethics are outlined, and an introduction is provided to the Australian codes of tendering practice. A questionnaire survey is then described which sought to ascertain the extent to which ethical behaviour in tendering is supported and practiced in Australia. The results of the survey indicate that most companies support the use of codes of tendering; defend the right of withdrawal of tenders; disapprove of bid shopping, cover pricing and union involvement in the tendering process, and support the principals' right to know what is included in a tender as well as the self-regulation of the tendering codes. It is also shown that most companies have developed, and follow, idiosyncratic ethical guidelines that are independent of, and often contrary to, the nationally prescribed codes. The conclusions recommend a need for the development of a theoretical frame of reference that can be tested through a more detailed empirical approach to the development of future ethical prescriptions in the field. © 1999 E & FN Spon.
Keywords: Ethics; Tendering; Codes; Restrictive practices